OCULAR DEFECTS IN FIRST GENERATION OF ETHANOL EXPOSED ALBINO RATS AND ITS PENETRANCE INTO THIRD GENERATION - Ismail, Muhammad; Janjua, Muhammad Zahoor (Journal of Ayub Medical College Abbottabad, 2004)
Background: The objective of this study was to observe the ocular teratogenic effects of alcohol on the third generation in albino rats. Methods: This study was carried out at department of Anatomy, Basic Medical Sciences Institute, JPMC Karachi from 1996-98. 36 pregnant female rats were divided into a treated and a control group (18 in each). The gestation period of albino rats is between 21-23 days (7 days trimester). Treated group was injected 25% alcohol (ethanol) intraperitonealy in a dose of 0.03 ml/gm body weight, while the control group was treated with normal saline in the same dose by same route. This intervention was done on 8th,9th and 10th gestational day. The first generation (n=115) was crossbred to get second generation (n=104) that was then used to produce the third generation (n=95). Generations of control rats were developed parallel. No treatment was given to the subsequent generations of treated or control groups. Results: Ocular defects (micro/macrophthalmia, cataract, coreanl opacity etc.) were observed in 30% (39/115) of the first generation, 40.38% (42/104) of the second generation and 45.26% (43/95) of 3rd generation of ethanol treated group. No ocular defect was observed in the three generations of controls. Conclusion: Alcohol exposure caused ocular defects in three generations of exposed rats. There is a need to study subsequent generations of rats for further penetranceand to develop cohort study in humans. KEY WORDS: Alcohol, Ocular defects, pregnancy, genetic defects.